Formation of a social tourism management system - Vorvul, Ju. V.; Pererva, P. G. (My University, 2023)
It is justified that a social tourism management system should offer mechanisms for evaluating planning effectiveness, be clear and accessible to personnel working in this area, and have flexibility and mobility to cover the maximum number of regions.
Формування системи управління соціальним туризмом
Keywords: tourism business; management; social aspect; management system